Correlation of the Quality of Antibiotic Usage by Utilising Gyssens Flow and The Success of Treatment in Negative Gram MDR Sepsis in Tertiary Hospital - Lardo, Soroy; Chen, Lie Khie; Santoso, Widayat Djoko; Rumende, Cleopas Martin (UI Scholars Hub, 2020)
Introduction. Multi Drug Resistance (MDR) antibiotics have become a global health threat to the community. The use of appropriate antibiotics makes preventive and curative measures very important for the success of overcoming MDR and intervening the complexity of resistance, at least slowing the rate of occurrence of MDR. This study aimed to identify the difference in the quality of antibiotic use quality of use using gyssens flowchart and the success in sepsis patients’ treatment due to gram-negative MDR bacteria with non-MDR bacterial infections in tertiary hospitals. Methods. A retrospective cohort study was conducted using secondary data from patient with age more or equal than 18 years who were hospitalized in inpatient unit or ICU in Indonesia Army Central Hospital Gatot Soebroto from 2017-2019. Both the MDR and non-MDR gram-negative inclusion groups were assessed for the quality of antibiotic using the Gyssen flowchart. Results. There was a significant difference between antibiotic quality on gram negative MDR bacteria and non-MDR (20.6% vs. 13.6%; RR 1.517 (CI 95% 1.1 – 2.1); p value = 0.015) which showed that gram-negative MDR experienced 1.517 times better quality than non-MDR. This study also found that there was a significant difference between therapeutic success on gram negative MDR bacteria and non-MDR (57.4% vs. 39.1%; RR 1,431 (CI 95% 1.0 – 2.1); p value = 0.02). Conclusions. There is a better quality on the utilization of antibiotics with Gyssens index patients resulted from MDR negative gram bacterial infection in comparison to non-MDR in tertiary hospital. There is also a better success in treating the sepsis patient with MDR negative gram bacterial infection in comparison with non-MDR.